Competent approach to the Economic education system continuously (Pedagogy of Higher and Secondary Education, 2014)
Madsigon V. V. Competent approach to the Economic education system continuously.The article examines the ways of improving the national economic development paradigm of education in the context of the renewal of its innovative system. The author justifies the theoretical and methodological basis for the formation of professional knowledge of future specialists in economics in the system of continuous education as an important condition for the development of the knowledge economy.
Keywords: education; economic education; paradigm; professional competence; experts in economics; a system of knowledge; innovation economy; continuous education; knowledge economy